2005
DOI: 10.1369/jhc.4a6556.2005
|View full text |Cite
|
Sign up to set email alerts
|

Localization of P2X and P2Y Receptors in Dorsal Root Ganglia of the Cat

Abstract: S U M M A R YThe distribution of P2X and P2Y receptor subtypes in upper lumbosacral cat dorsal root ganglia (DRG) has been investigated using immunohistochemistry. Intensity of immunoreactivity for six P2X receptors (P2X 5 receptors were immuno-negative) and the three P2Y receptors examined in cat DRG was in the order of P2Y 2 ϭ P2Y 4 Ͼ P2X 3 Ͼ P2X 2 ϭ P2X 7 Ͼ P2X 6 Ͼ P2X 1 ϭ P2X 4 Ͼ P2Y 1 . P2X 3 , P2Y 2 , and P2Y 4 receptor polyclonal antibodies stained 33.8%, 35.3%, and 47.6% of DRG neurons, respectively. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…In addition, we found that 64 % of P2X 3 receptor-expressing trigeminal ganglion neurons also express IB4, suggesting that they are mainly non-peptidergic, unmyelinated afferents, since IB4 labelling is almost entirely limited to non-peptide unmyelinated afferents in the rat (Ambalavanar and Morris, 1993;Kitchener et al, 1993;Kitchener et al, 1994;Stucky and Lewin, 1999;Gerke and Plenderleith, 2001). This proportion is in agreement with previous reports in the rat ( Vulchanova et al, 1998;Novakovic et al, 1999) and cat (88 %, Ruan et al, 2005). In rat DRG, P2X 3 is expressed by few (1-3 %) peptide containing neurons (Bradbury et al, 1998;Vulchanova et al, 1998).…”
Section: Discussion P2x 2 and P2x 3 Receptors Are Predominantly Locatsupporting
confidence: 93%
“…In addition, we found that 64 % of P2X 3 receptor-expressing trigeminal ganglion neurons also express IB4, suggesting that they are mainly non-peptidergic, unmyelinated afferents, since IB4 labelling is almost entirely limited to non-peptide unmyelinated afferents in the rat (Ambalavanar and Morris, 1993;Kitchener et al, 1993;Kitchener et al, 1994;Stucky and Lewin, 1999;Gerke and Plenderleith, 2001). This proportion is in agreement with previous reports in the rat ( Vulchanova et al, 1998;Novakovic et al, 1999) and cat (88 %, Ruan et al, 2005). In rat DRG, P2X 3 is expressed by few (1-3 %) peptide containing neurons (Bradbury et al, 1998;Vulchanova et al, 1998).…”
Section: Discussion P2x 2 and P2x 3 Receptors Are Predominantly Locatsupporting
confidence: 93%
“…UTP is an agonist for P2Y 2 and P2Y 4 receptors [29]. P2Y 4 , a Gq-coupled UTP receptor, is expressed in sensory ganglia [33,34], but functional analysis shows low levels of P2Y 4 receptor expression in DRG neurons [8,35]. Suramin has been shown to block all nucleotide-sensitive P2Y receptors with the exception of the P2Y 4 receptor subtype [30].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the population of DRG neurons that express CGRP, only 14-26% express P2X 3 (Bradbury et al, 1998;Ruan et al, 2005). In trigeminal neurons expressing CGRP, about 80% co-express P2X 3 (Fabbretti et al, 2006).…”
Section: Deep-tissue Craniofacial Peptidergic Afferent Neurons Co-expmentioning
confidence: 99%